Dynamics of small scale spin systems in hexagonal-triangular, tetrahedral & linear chain geometries - Cañeso, Diane M. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2014)
We investigate the evolution of the magnetization probability of a frustrated Ising antiferromagnet in different geometrics, both in the absence and in the presence of an external magnetic field. We set the rate of spin evolution from the Glauber model, both in discrete and continuous time cases. We derive the transition probability matrix and calculate the evolution of the magnetization probability for various initial conditions and in three main regimes.